2015
DOI: 10.1044/2015_ajslp-13-0138
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' and Mothers' Verbal Responsiveness and the Language Skills of Young Children With Autism Spectrum Disorder

Abstract: Purpose In this observational study, we examined the interactions of 16 young children with autism spectrum disorder (ASD) and their parents to investigate (a) differences in verbal responsiveness used by fathers and mothers in interactions with their children with ASD and (b) concurrent associations between the language skills of children with ASD and the verbal responsiveness of both fathers and mothers. Method Parent verbal responsiveness was coded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 55 publications
4
53
2
Order By: Relevance
“…This is important because greater language ability facilitates more meaningful social interaction and increased adaptive functioning [Anderson et al, ; Kasari et al, ; Luyster, Kadlec, Carter, & Tager‐Flusberg, ; McDuffie, Yoder, & Stone, ]. Among older children with ASD (i.e., over 3 years), there is a consistent relation between PVR and child communication [Flippin & Watson, ; Fusaroli, Weed, Fein, & Naigles, ; Siller & Sigman, , ; Walton & Ingersoll, ]. For example, Siller and Sigman [, ] found that parents' follow‐in commenting was the best predictor of long‐term language for children with ASD ages 3–5 years, controlling for cognitive abilities, joint attention, and initial levels of language.…”
Section: Pvr and Child Communication In Asdmentioning
confidence: 99%
“…This is important because greater language ability facilitates more meaningful social interaction and increased adaptive functioning [Anderson et al, ; Kasari et al, ; Luyster, Kadlec, Carter, & Tager‐Flusberg, ; McDuffie, Yoder, & Stone, ]. Among older children with ASD (i.e., over 3 years), there is a consistent relation between PVR and child communication [Flippin & Watson, ; Fusaroli, Weed, Fein, & Naigles, ; Siller & Sigman, , ; Walton & Ingersoll, ]. For example, Siller and Sigman [, ] found that parents' follow‐in commenting was the best predictor of long‐term language for children with ASD ages 3–5 years, controlling for cognitive abilities, joint attention, and initial levels of language.…”
Section: Pvr and Child Communication In Asdmentioning
confidence: 99%
“…Given social and communication difficulties in children with ASD, their parents may feel incompetent in their ability to establish an emotional connection with them. Additionally, the quality of involvement of the parents is an important variable for the ability of children with ASD to participate in play [ 22 24 ] and can also benefit the parents. Parents of young children with ASD that actively participate in coaching processes or guided educational treatments based on the use of strategies to maximize engagement opportunities with their child exhibit increased competence and higher levels of effect [ 13 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that, although both mothers and fathers used similar proportions of responsive play behavior and use of both parents' verbal and play behaviors correlated significantly with higher-level child object play, the use of responsive play behavior was correlated with higherlevel object play only for fathers. However, a follow-up study by Flippin and Watson (2015) indicated that mothers of children with ASD were more responsive than were fathers of children with ASD on the basis of both frequency of verbal responses and a proportion of child initiations. Furthermore, those children initiated more leads with their mothers than with their fathers during play interactions.…”
Section: Discussionmentioning
confidence: 99%